Challenges facing Supply Chain Performance at Department of Defence in the Republic of South Africa - Matakalatse, Moloantoa (University of the Witwatersrand, Johannesburg, 2024)
The purpose of the study is to gain insights into the perception of supplier performance management in the Department of Defence supply chain and subsequently to find out the public supply chain challenges faced by end-users within the Department of Defence (DOD) and to propose the solutions thereof. The problem is that the clients (receiving departments) are continuously receiving poor standards and quality of public goods and services on behalf of Service and Division within the DOD. Lack of sufficient suppliers’ development framework and programme especially the SMMEs in DOD is also causing poor supplier performance. Objective 1: Investigating Supplier Performance Challenges. Objective 2: Impacts of Supplier Performance Challenges. Objective 3: Potential Solution. Research Method: The researcher used a qualitative method to conduct the study. Manual Thematic Analysis was used to analyse the data. The discussion, results and findings: the results of interviews conducted with 15 officials from the Department of Defence (DOD) regarding the issues faced in supply chain performance due to inadequate performance by suppliers. The qualitative data analysis identified three primary themes for each of the research objectives in the study. The results suggest that inadequate financial resources, insufficient supplier expertise, and challenges in planning and communication are major contributors to subpar supplier performance within the Department of Defence (DOD) supply chain. Consequently, this leads to interruptions, setbacks, inefficient use of resources, and adverse effects on financial plans and expenditures. In response to these difficulties, attendees suggested potential remedies such as implementing supplier development initiatives, strengthening performance monitoring measures, and implementing fines for suppliers that fail to meet expectations. Conclusion and recommendations: A comprehensive approach is necessary, involving the provision of development assistance, the enhancement of oversight, and the careful enforcement of compliance. Utilising developmental strategies to enhance financial stability, knowledge, and collaborative efficacy holds great potential for generating systemic enhancements
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Supply Chain Management; Supply Chain Performance; Poor Supplier Performance; Supplier Development; Supplier Performance Measurement and Monitoring; Financial Constraints; Buyer-Supplier Relationship; SDG-8: Decent work and economic growth